A case of twenty nail dystrophy affecting a 12 year old boy - Shanmuganathan, Harshitha; Kumar, Radha (International Journal of Contemporary Pediatrics, 2019)
Nail diseases in children may be congenital or acquired and occurs in 3 to 11% of pediatric population. Twenty nail dystrophy is a nail disorder with a classical presentation, often affecting all twenty nails. It is an idiopathic disorder in childhood but can be associated with other diseases such as lichen planus, alopecia areata, psoriasis, eczema, IgA deficiency, atopic dermatitis, ichthyosis vulgaris and vitiligo. Twenty nail dystrophy is otherwise called trachyonychia. Typically, the condition is bilateral and symmetrical affecting all the nails of hands and feet. It is cosmetically disfiguring and can be source of anxiety for children and parents, which can impact further the quality of life. Twenty nail dystrophy is of two types, based on the clinical presentation namely opaque or shiny trachyonychia. Since this nail disorder is associated with a number of dermatologic diseases, children require long term follow up. We report a case of a 12-year-old boy with a three-year history of twenty nail dystrophy with no relevant family history of skin or nail diseases. The child had isolated nail manifestation without any other dermatologic condition. Twenty nail dystrophy is a self-limiting disease, which is treated conservatively. The aim of this report is to highlight importance of a thorough physical examination to diagnose nail disorders in early stages, which will be helpful to clinicians to distinguish the different nail conditions and associated illness and decide on the correct management. It is important to counsel the family about the benign nature of the disease and good prognosis.